2022
DOI: 10.1111/ecc.13719
|View full text |Cite
|
Sign up to set email alerts
|

How can advance care planning support hope in patients with advanced cancer and their families: A qualitative study as part of the international ACTION trial

Abstract: Objective: Clinicians' fears of taking away patients' hope is one of the barriers to advance care planning (ACP). Research on how ACP supports hope is scarce. We have taken up the challenge to specify ways in which ACP conversations may potentially support hope. Methods:In an international qualitative study, we explored ACP experiences of patients with advanced cancer and their personal representatives (PRs) within the cluster-randomised control ACTION trial. Using deductive analysis of data obtained in interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Descriptive analysis revealed that two in three patients considered the ACP conversations to be ‘quite or very helpful’, while one in six patients found them to be ‘quite or very stressful’ [ 18 ▪ ]. Qualitative analyses of patient and caregiver interview content showed that ACP conversation participation does not require patients to be ready to address all ACP topics [ 21 ], and that ACP potentially supports hope [ 22 ] and allows patients and caregivers to share mutual understanding and concerns [ 23 ].…”
Section: Main Randomized Controlled Trial Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Descriptive analysis revealed that two in three patients considered the ACP conversations to be ‘quite or very helpful’, while one in six patients found them to be ‘quite or very stressful’ [ 18 ▪ ]. Qualitative analyses of patient and caregiver interview content showed that ACP conversation participation does not require patients to be ready to address all ACP topics [ 21 ], and that ACP potentially supports hope [ 22 ] and allows patients and caregivers to share mutual understanding and concerns [ 23 ].…”
Section: Main Randomized Controlled Trial Characteristicsmentioning
confidence: 99%
“…The cancer care contexts, intervention modalities, and main outcomes were heterogeneous. The interventions were primarily multimodal and of three main types: those that aimed to improve ACP uptake via patient/caregiver-oriented tools (three RCTs) [12–16], those involving trained ACP facilitators’ support of patients and caregivers [six RCTs, including one targeting adolescent and young-adult (AYA) patients] [17,18 ▪ ,19–37], and one involving the prompting of trained physicians’ implementation of ACP discussions in practice (one RCT) [38,39 ▪ ,40–42]. Patient, caregiver, HCP, and healthcare service outcomes were measured.…”
Section: Main Randomized Controlled Trial Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations